Ethnographic Study of Perspective and Attitude of Breastfeeding Mothers Towards the use of Elaeis Guineensis Sap As Galactagogue Among Igbo Women of Southeastern Nigeria - Chikezie, Okamkpa Jude; Chike, Anibeze Ikechukwu; Ignatius, Ozor Ikemefuna; Ndu, Ikenna Kingsely; Umeh, Uchenna Anthony (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: As an age-old traditional practice, nursing mothers from southeastern Nigeria use the Elaeis guineensis sap (from the oil palm tree also referred to as palm wine) to induce and sustain lactation a few hours after delivery. This practice is still ongoing to date, despite the scarcity of clinical data supporting its efficacy and safety. This study aimed to generate preliminary data on the prevalence, perceptions, and behaviors related to the use of Elaeis guineensis sap as a galactagogue. STUDY DESIGN: Mothers who had breastfed or breastfeeding at the time of the survey, were invited to complete a questionnaire that asked about their, perceptions, efficacy, and possible side effects of Elaeis guineensis sap on both mother and child during breastfeeding. Chi-square analysis was used to conduct data analysis. RESULT: A total of 5002 mothers completed the survey with 61% reporting use of Elaeis guineensis sap (palm wine) following parturition. Most of the respondents (73%) attained tertiary education. The practice was mostly recommended by direct relatives (38%) while the commonest reason for this practice was perceived insufficient milk production (32.2%). The majority of the respondents (52%) were satisfied with the outcome while 44% reported no negative side effects. CONCLUSION: The use of Elaeis guineensis sap by mothers following parturition is common in south-eastern Nigeria. However, randomized control studies are needed to provide evidence for the efficacy and safety of this plant product. This will be relevant to the formation of intercultural health policies which will value and respect the positive cultural practices of a people.